Utilization of biodiesel residue through efficient microwave-assisted synthesis of carbon quantum dots: A versatile nanomaterial for environmental remediation - Portela, Carolina Inácio; Vieira, Nirton Cristi Silva; Brazil, Tayra Rodrigues [UNESP]; Giroto, Amanda Soares; Gabriel Filho, José Balena; Gonçalves, Maraísa (Elsevier, 2025)
The rapid expansion of the biodiesel industry has substantially increased crude glycerol residue (CG) production, creating sustainability and economic challenges due to surplus glycerol generation. Conventional purification methods are costly and environmentally demanding, necessitating innovative strategies to utilize this residue effectively. This study innovates by exploring the microwave-assisted synthesis of carbon dots (CDs) from CG, exemplifying a shift toward sustainable biodiesel production by transforming the residue into a multifunctional material. CDs exhibited a nanometric spherical morphology of 2.6 ± 0.3 nm diameter verified by HRTEM analysis. The reduction of oxygen confirmed the transformation of CG into CDs–H bands and the formation of polyaromatic structures. The graphitic structures were verified by Raman spectroscopy, electron paramagnetic resonance, and X-ray diffraction. The quantum yield (QY) was calculated to be 1.3%. The multifunctionality of CDs has been proven in sensing and photocatalysis. In the sensor applications, the CDs demonstrated strong fluorescence quenching in the presence of Fe3+ and Cu2+ ions, with a limit of detection of 1.80 ± 0.01 and 4.00 ± 0.04 mg.L−1, respectively, indicating the potential use of CDs in detecting these ions in wastewater samples. When complexed with titanium dioxide (TiO2), the TiO2/CDs composite showed an extended photoresponse of TiO2 to the UV–visible region, improving the efficiency of photocatalytic reactions for Victoria Blue B (VBB) dye degradation (98% degradation after 150 min). This research highlights the potential of utilizing CG to produce versatile CDs, contribute to more sustainable biodiesel production, and offer promising applications in environmental sensing and photocatalysis.
Keywords: Biodiesel residue; Carbon dots; Crude glycerol; Microwave pyrolysis; Photocatalysis; Sensor